Uganda : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents findings of Uganda's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, and Payment Systems. The banking system in Uganda, which dominates the financial system, is fundamentally sound, more resilient than in the past, and currently poses no threat to macroeconomic stability. A major disruption in donor flows could, however, challenge macroeconomic stability and threaten the financial system.